Leaching method of high matte nickel, positive electrode material precursor, and preparation method and application of positive electrode material precursor

Through the self-heating reaction between high ice nickel and oxidant and low acid leaching process, combined with magnetic separation and co-precipitation, the problems of high ice nickel leaching rate and high process cost are solved, and an efficient and safe leaching process is achieved, and high-quality leaching process is prepared. Precursor of positive electrode material.

CN119242943AActive Publication Date: 2025-01-03HUNAN BRUNP RECYCLING TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411383032.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing high ice nickel leaching process has problems such as low leaching rate, high process cost, high equipment requirements and low safety. Traditional high ice nickel pretreatment requires additional heat source and high energy consumption.

Method used

The high ice nickel is mixed with an oxidant for self-heating reaction, and a low acid leaching is performed, and the pH value is controlled to be 0.5-1.0. The heat generated by the auto-heating reaction is used to replace the external heat source, and the positive electrode material precursor is prepared by magnetic separation and co-precipitation.

Benefits of technology

The leaching rate is significantly improved, process cost is reduced, equipment requirements are simplified, process safety is improved, and the use of auxiliary materials is reduced through self-heating reaction and magnetic separation, and the leaching efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242943A_ABST
    Figure CN119242943A_ABST
Patent Text Reader

Abstract

The invention discloses a leaching method of high matte nickel, a positive electrode material precursor, a preparation method and application, and relates to the technical field of pyrometallurgy and hydrometallurgy. The high-grade matte nickel is mixed with an oxidizing agent for a self-heating reaction, the oxidizing agent serves as a raw material to provide an oxidation effect, and meanwhile heat generated by the self-heating reaction replaces an external heat source. The pretreatment powder can be subjected to one-time low-acid leaching under the normal-pressure condition, and due to the fact that acid is added into the material obtained after the high-grade matte nickel and the oxidizing agent potassium permanganate are subjected to the self-heating reaction, leaching is extremely easy, a large number of auxiliary materials do not need to be added for assisting low-acid leaching basically, high-acidity leaching does not need to be conducted, and cost is reduced. Compared with the conventional high-pressure oxygen leaching reaction, the leaching process provided by the invention has the advantages that the requirement on equipment is lower, the leaching time is shortened, the leaching efficiency is improved, and nickel oxide is formed by most of high-grade matte nickel in the reaction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pyrometallurgy and hydrometallurgy, and in particular to a leaching method of high-matte nickel, a positive electrode material precursor, a preparation method and an application thereof. Background Art

[0002] With the rapid development of new energy technologies, the demand for high-nickel products is growing. Providing new nickel sources has a stabilizing effect on the industrial chain system. High-grade nickel matte and nickel iron are good choices for new nickel sources.

[0003] High-grade nickel matte is a eutectic of nickel, copper, cobalt, iron and sulfur metal sulfides obtained by primary smelting of nickel concentrate through electrolysis and conversion. The nickel, copper and cobalt phases mainly exist in the form of sulfide phases and alloy phases. Because of the high nickel content (55%-65%), it is called high-grade nickel matte, and the one with low nickel content is low-grade nickel matte. It is mainly used in the production of electrolytic nickel, nickel oxide, nickel iron, nickel-containing alloys and various nickel salts. It can also be directly used for steelmaking after special treatment. Nickel iron NPI is an important nickel-iron alloy product, usually containing about 4-10% nickel, and is mainly used in the production of stainless steel, alloy steel, high-temperature alloys, battery materials and other fields. Its main raw material is nickel iron ore, which contains nickel and iron and is commonly found in the Philippines, Indonesia and New Caledonia. It is not difficult to see that high-grade nickel matte is only a transition, and the ultimate goal is to produce nickel sulfate, which is an essential material for the production of ternary precursors, and the ternary precursors eventually generate the positive electrode materials of the battery. Starting from natural nickel ore, it eventually becomes the positive electrode material, going through a complex and lengthy processing process, and each processing process can become a sub-industry.

[0004] The high-pressure acid leaching process is usually used in the leaching of high-grade nickel matte. High-pressure acid leaching has high requirements on equipment working conditions, large slag volume, large equipment volume, high manufacturing cost, and low safety. The traditional high-grade nickel matte is leached with low acid once, and the leaching rate is only 20% to 50%, and the leaching time is long. It is necessary to develop an efficient, fast, safe and economical leaching method. In addition, if oxidative roasting is used for the pretreatment of high-grade nickel matte, an additional heat source is required, which has high energy consumption and high economic cost.

[0005] In addition, the common ternary precursors on the market are hydroxides composed of three metal elements: nickel, cobalt and manganese. The ratio of each element determines the performance of the ternary precursor. Today, the new energy vehicle industry is developing rapidly, and there is a strong demand for high-capacity lithium-ion batteries, which puts forward requirements for the performance of front-end ternary positive electrode materials. High-nickel ternary precursors have gradually become the mainstream. Developing new leaching methods to reduce the cost of synthesizing ternary precursors is the development direction of the industry.

[0006] In summary, there is an urgent need to develop an efficient, fast, safe and economical high-nickel matte leaching process to significantly improve the leaching rate while reducing the process cost.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The purpose of the present invention is to provide a leaching method for high-matte nickel, a positive electrode material precursor, a preparation method and an application, aiming to significantly improve the leaching rate while reducing the process cost.

[0009] The present invention is achieved in that:

[0010] In a first aspect, the present invention provides a method for leaching high-grade nickel matte, comprising:

[0011] Raw material pretreatment: Mix high nickel matte with oxidant for autothermal reaction;

[0012] Primary low-acid leaching: The powder obtained by pre-treatment of the raw material is subjected to a primary low-acid leaching without pressurization, and the pH value of the leaching is controlled to be 0.5-1.0.

[0013] In an optional embodiment, the process of raw material pretreatment includes: subjecting high-grade nickel matte to a magnetic separation to obtain nickel iron and high-grade nickel matte powder; mixing the high-grade nickel matte powder with an oxidant and a buffer for autothermal reaction to obtain a pretreatment intermediate powder; subjecting the pretreatment intermediate powder to a secondary magnetic separation to obtain a pretreatment powder;

[0014] During the raw material pretreatment process, at least one of the characteristics A1 to A7 is met:

[0015] Feature A1: Firstly, the high-grade nickel matte is crushed to a particle size of 100-400 mesh, and then magnetic separation is performed;

[0016] Feature A2: The oxidizing agent is selected from at least one of potassium permanganate and sodium permanganate;

[0017] Feature A3: The mass ratio of high nickel matte powder to oxidant is 1:(1-3);

[0018] Feature A4: The buffer is selected from at least one of calcium carbonate and calcium hydroxide;

[0019] Feature A5: The mass ratio of the buffer to the total amount of the high nickel matte powder and the oxidant is (1-10): 100;

[0020] Feature A6: The reaction time of the autothermal reaction is 50min-120min;

[0021] Feature A7: The autothermal reaction is carried out under air atmosphere.

[0022] In an optional embodiment, the process of a low-acid leaching comprises: leaching the pre-treated powder in a sulfuric acid solution;

[0023] After 1h-2h of reaction, the first solid-liquid separation is performed;

[0024] Or, after reacting for 1h-2h, add pre-treated powder to adjust the pH value to 2.0-2.5, react for 2h-3h, and then perform the first solid-liquid separation;

[0025] Alternatively, after reacting for 0.5 h to 2.0 h, crude nickel hydroxide or crude cobalt hydroxide is added to adjust the pH value to 2.0 to 2.5, reacting for 2 h to 3 h, and then performing the first solid-liquid separation.

[0026] In an optional embodiment, the pre-treated powder is mixed with water and concentrated sulfuric acid, and the resulting slurry is reacted at a pH value of 0.5-1.0;

[0027] During a low-acid leaching process, at least one of the characteristics B1 to B5 is met:

[0028] Feature B1: The mass ratio of pre-treated powder to water is 1:(1-4);

[0029] Feature B2: The mass ratio of the pre-treated powder to the concentrated sulfuric acid is 1:(1.0-1.5), and the mass fraction of the concentrated sulfuric acid is greater than or equal to 98%;

[0030] Feature B3: The reaction temperature of the primary low-acid leaching is 50°C-90°C;

[0031] Feature B4: Before the first solid-liquid separation, the temperature of the material after the reaction is adjusted to 80°C-90°C;

[0032] Feature B5: The first solid-liquid separation is carried out in a membrane filter press.

[0033] In an optional embodiment, the method further comprises: mixing the primary low-acid leaching residue obtained by the first solid-liquid separation with sulfuric acid to adjust the pH value to 0.5-1.0, adjusting the temperature to 50° C.-70° C., and then mixing with a reducing agent for reaction, repeatedly adding sulfuric acid and a reducing agent to adjust the pH value to 0.5-1.0, and performing secondary low-acid leaching;

[0034] Preferably, after the secondary low-acid leaching reaction is completed, a second solid-liquid separation is performed to obtain a secondary low-acid leaching liquid and a secondary low-acid leaching residue; the secondary low-acid leaching liquid is returned to the primary low-acid leaching stage and mixed with the pre-treated powder to prepare a slurry;

[0035] Preferably, the reducing agent is a hydrogen peroxide solution with a mass fraction of 8%-30%.

[0036] In an optional embodiment, the primary low-acid leaching solution obtained by the first solid-liquid separation is subjected to sequential copper removal, ferrous iron removal and iron-aluminum removal to obtain a decontaminated leaching solution;

[0037] Preferably, the copper removal process comprises: mixing a low-acid leaching solution with nickel-iron element or nickel-iron powder for reaction for 1h-2h, then adding sulfuric acid to adjust the pH value to 0.5-1.0, and standing for 2h-4h to obtain a copper removal solution;

[0038] More preferably, the pH is stabilized for 1 h to 4 h under stirring before standing for 2 h to 4 h;

[0039] More preferably, by regulating the amount of nickel iron or nickel iron powder added, the molar ratio of the total amount of nickel iron added to the copper ions in the primary low-acid leaching solution is 1: (0.5-1.5);

[0040] More preferably, the particle size of the nickel-iron powder is 60 mesh to 200 mesh.

[0041] In an optional embodiment, the liquid after the copper removal is mixed with a hydrogen peroxide solution to remove ferrous iron, and the temperature is raised to 80°C-95°C and the pH value is adjusted to 3.8-4.5 to deeply remove iron and aluminum, and then the calcium, magnesium, zinc and copper are removed by extraction;

[0042] Preferably, the process of removing ferrous iron includes: heating the solution after the copper removal to 80°C-95°C, adding nickel hydroxide to adjust the pH value to 2.0-3.0, and adding a hydrogen peroxide solution with a mass fraction of 8%-30% to remove the remaining ferrous iron ions;

[0043] Preferably, the pH value is adjusted to 3.8-4.5 by adding sodium carbonate solution.

[0044] In a second aspect, the present invention provides a method for preparing a positive electrode material precursor, comprising using the leaching solution obtained by any leaching method in the aforementioned embodiment as a raw material, and adopting a coprecipitation method to prepare a positive electrode material precursor;

[0045] Preferably, metal salts are added to the leaching solution, and complexing agents and precipitants are added during the coprecipitation reaction.

[0046] In a third aspect, the present invention provides a positive electrode material precursor prepared by the preparation method of the aforementioned embodiment.

[0047] In a fourth aspect, the present invention provides a positive electrode material prepared by the positive electrode material precursor of the aforementioned embodiment.

[0048] The present invention has the following beneficial effects: high-matte nickel is mixed with an oxidant to undergo a self-heating reaction. The oxidant, as a raw material, not only provides an oxidizing effect, but also the heat generated by the self-heating reaction replaces the external heat source. The pre-treated powder can be subjected to a low-acid leaching under normal pressure conditions. Since the material after the self-heating reaction of high-matte nickel and the oxidant potassium permanganate is easily leached by adding acid, there is basically no need to add a large amount of auxiliary materials to assist the low-acid leaching, nor is there a need for high-acid leaching, thereby reducing costs. Compared with conventional high-pressure oxygen leaching reactions, the leaching process provided by the present invention has lower equipment requirements, shortened leaching time, and improved leaching efficiency. During the reaction process, most of the high-matte nickel forms nickel oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0050] Figure 1 The present invention is a flowchart of a method for leaching nickel matte according to an embodiment of the present invention. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0052] In response to the problems of low leaching rate and high process cost resulting from the need for high pressure assistance in the traditional high-grade nickel matte leaching process, the inventors optimized the high-grade nickel matte leaching method and especially adjusted the steps of the raw material pretreatment process so that the pre-treated powder obtained in the raw material pretreatment process can be leached under normal pressure conditions and the leaching rate is significantly improved.

[0053] Please refer to Figure 1 The embodiment of the present invention provides a method for leaching high-grade nickel matte, comprising the following steps:

[0054] S1. Raw material pretreatment

[0055] The raw material pretreatment process provided by the embodiment of the present invention mainly includes the following three steps: primary magnetic separation, autothermal reaction and secondary magnetic separation. High-grade nickel matte mainly contains alloy phase and sulfide phase. The nickel-iron element is removed by primary magnetic separation, so that the sulfide phase is enriched for autothermal reaction. The sulfides that are difficult to leach in the high-grade nickel matte material are basically oxidized, and the leaching efficiency is greatly improved. After the reaction, the iron sulfide in the sulfide phase reacts to obtain ferroferric oxide, which is removed by secondary magnetic separation.

[0056] In some embodiments, the nickel matte is crushed to a particle size of 100-400 mesh (such as 100 mesh, 200 mesh, 300 mesh, 400 mesh, etc.), and then subjected to a magnetic separation to obtain nickel iron and nickel matte powder. A magnetic separation is performed using nickel matte with a smaller particle size to fully remove the nickel iron and improve the purification effect of the magnetic separation. Specifically, a magnetic separation can be performed in a commercially available magnetic separator, and the magnetic separation parameters can be set according to the preferred parameters of the equipment. The nickel iron powder obtained by a magnetic separation can be used for copper removal in a subsequent impurity removal process, which reduces the elemental content in the nickel matte, improves the utilization rate of the nickel matte, reduces the consumption of auxiliary materials, and the oxidant required for the high nickel matte powder after magnetic separation is also reduced accordingly, and the process cost is lower.

[0057] The high nickel matte powder obtained by the primary magnetic separation is mixed with an oxidant and a buffer for autothermal reaction to obtain a pre-treatment intermediate powder; the pre-treatment intermediate powder is then subjected to secondary magnetic separation to obtain a pre-treatment powder. When the low-acid leaching slurry is filtered in the conventional leaching method, the presence of a small amount of oil and iron in the slurry will affect the filtration of the diaphragm filter press. The high temperature generated by the autothermal reaction of the embodiment of the present invention promotes the decomposition of organic matter, and iron is converted into ferroferric oxide, which is removed by magnetic separation, which is more cost-effective and solves the problem of difficult filtration. In addition, the secondary magnetic separation also reduces the impurities in the low-acid leaching raw materials, reducing the cost of subsequent iron removal.

[0058] In some embodiments, the oxidant is selected from at least one of potassium permanganate and sodium permanganate, and the oxidant can be any one or more of the above. The mass ratio of high-matte nickel powder to oxidant is 1: (1-3), such as 1: 1, 1: 2, 1: 3, etc. High-matte nickel powder reacts with the oxidant in an autothermal manner, and the heat of the reaction process comes from the reaction itself, saving a lot of electricity. The reaction speed is faster than the traditional heating method. By adjusting the raw material ratio to make the combustion reaction complete, the center temperature can reach above 1000°C.

[0059] In some embodiments, the buffer is selected from at least one of calcium carbonate and calcium hydroxide, and the buffer can be any one or more of the above. The mass ratio of the buffer to the total amount of high nickel matte powder and oxidant is (1-10): 100. The amount of the buffer is calculated based on the total amount of high nickel matte powder and oxidant, so that the mass ratio of the buffer to the total amount of high nickel matte powder and oxidant can be 1:100, 3:100, 5:100, 8:100, 10:100, etc. The addition of buffers such as calcium carbonate in the pre-treatment process can not only regulate the speed of the autothermal reaction and reduce the reaction risk factor, but also absorb the sulfur dioxide produced by the reaction of high nickel matte and oxidant, which greatly reduces the safety risk of the process and better meets environmental protection requirements.

[0060] In some embodiments, the reaction time of the autothermal reaction is 50 min-120 min, specifically 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc. The autothermal reaction time is terminated when the oxidant or high nickel matte is consumed. The autothermal reaction can be carried out in an air atmosphere, which is convenient to operate.

[0061] It should be added that, compared with high nickel matte which uses lithium cobalt oxide or ternary positive electrode materials as auxiliary materials for roasting, the oxidant potassium permanganate in the embodiment of the present invention has a single phase, does not contain copper, iron, and aluminum impurities, and its oxidizing property is much higher than that of the ternary positive electrode material. The pre-treatment process uses two magnetic separations, which has lower cost than roasting. The alloy phase nickel and iron obtained by the first magnetic separation can be used for the subsequent copper removal, and the second magnetic separation removes the ferroferric oxide. While removing impurities, there is no need to consider lithium recovery at the back end of the extraction process, and the overall process route is optimized and upgraded.

[0062] S2, primary low acid leaching

[0063] The pre-treated powder is subjected to a low-acid leaching without pressurization, and the pH value of the leaching is controlled to be 0.5-1.0. Since the material after the autothermal reaction between high-matte nickel and oxidants such as potassium permanganate is easily leached by adding acid, there is basically no need to add a large amount of auxiliary materials to assist low-acid leaching, nor is there a need for high-acid leaching, which reduces the process cost. Compared with conventional high-pressure oxygen leaching reactions, the requirements for equipment are lower, the leaching time is shortened, and the leaching efficiency is improved. Most of the high-matte nickel forms nickel oxide during the reaction. Although the method provided in the embodiment of the present invention is leaching at normal pressure, the leaching efficiency is close to that of high-pressure leaching, the equipment requirements are simple, and the cost is lower.

[0064] Specifically, the leaching pH value of the primary low-acid leaching can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc.

[0065] In some embodiments, the pre-treated powder is mixed with water and concentrated sulfuric acid, and the resulting slurry is reacted at a pH of 0.5-1.0. Since the temperature of the reactor (such as a crucible) after the autothermal reaction is relatively high, the crucible of the autothermal reaction can be used to mix water with part of the pre-treated powder to make a slurry, and water can be sprayed into the crucible, and the crucible can be cooled by spraying water, and the residual heat can be used to indirectly increase the temperature, thereby reducing the amount of steam required for subsequent heating of the feed liquid, and the resulting slurry can be introduced into the corresponding reaction tank for batching.

[0066] In some embodiments, during a low-acid leaching process, the mass ratio of the pre-treatment powder to water is 1: (1-4), such as 1: 1, 1: 2, 1: 3, 1: 4, etc. The mass ratio of the pre-treatment powder to concentrated sulfuric acid is 1: (1.0-1.5), such as 1: 1.0, 1: 1.1, 1: 1.2, 1: 1.3, 1: 1.4, 1: 1.5, etc., and the mass fraction of the concentrated sulfuric acid is greater than or equal to 98%, such as commercially available concentrated sulfuric acid with a mass fraction of 98%. By regulating the amount of pre-treatment powder, water, and concentrated sulfuric acid, the reaction is fully carried out and the leaching rate of nickel is improved.

[0067] Furthermore, the reaction temperature of the primary low-acid leaching is 50°C-90°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, etc., which is beneficial to further improve the leaching effect within this temperature range.

[0068] In some embodiments, one-time low-acid leaching can adopt the following three processes:

[0069] (1) After reacting for 1-2 hours, the first solid-liquid separation is performed to obtain a primary low-acid leaching residue and a primary low-acid leaching liquid. Specifically, the reaction time can be 1 hour, 2 hours, 3 hours, etc.

[0070] (2) After reacting for 1-2 hours, add pre-treated powder to adjust the pH value to 2.0-2.5, react for 2-3 hours, and then perform the first solid-liquid separation. Specifically, after adding pre-treated powder to adjust the pH value, the pH value can be 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, etc., and the reaction time can be 2.0 hours, 2.5 hours, 3.0 hours, etc.

[0071] (3) After reacting for 0.5h-2.0h, crude nickel hydroxide MHP or crude cobalt hydroxide is added to adjust the pH value to 2.0-2.5, react for 2h-3h, and then perform the first solid-liquid separation. Crude nickel hydroxide MHP or crude cobalt hydroxide is a commercially available raw material. After adjusting the pH, the pH value can be 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, etc., and the reaction time can be 2.0h, 2.5h, 3.0h, etc.

[0072] Among the above three processes, the use of processes (2) and (3) can further improve the leaching rate and increase the raw material utilization rate.

[0073] In some embodiments, before the first solid-liquid separation, the temperature of the material after the reaction is adjusted to 80°C-90°C, such as 80°C, 83°C, 85°C, 88°C, 90°C, etc. Since the slurry concentration is high, crystals are easily generated at low temperatures to block the solid-liquid separation equipment. Appropriately heating before solid-liquid separation can avoid the generation of crystals. The first solid-liquid separation can be performed in a membrane filter press, but is not limited thereto.

[0074] S3. Primary low acid leaching slag treatment

[0075] The primary low-acid leaching residue still contains a small amount of valuable metals, so secondary low-acid leaching can be carried out to improve the utilization rate of raw materials.

[0076] In some embodiments, the low-acid leaching residue obtained by the first solid-liquid separation is mixed with sulfuric acid to adjust the pH value to 0.5-1.0, and the temperature is adjusted to 50°C-70°C and then mixed with a reducing agent for reaction. After the reducing agent is added, the pH value rises, and sulfuric acid needs to be added to adjust the pH value, and then a reducing agent is added, and then sulfuric acid is added to adjust. Sulfuric acid and a reducing agent are repeatedly added to make the pH value 0.5-1.0, and a secondary low-acid leaching is performed. There is high-valent manganese in the low-acid leaching residue, and sulfuric acid and a reducing agent are added to leach it again to increase the leaching rate of valuable metals. Specifically, the leaching pH value of the secondary low-acid leaching can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc., and the leaching temperature can be 50°C, 55°C, 60°C, 65°C, 70°C, etc.

[0077] In some embodiments, the reducing agent is a hydrogen peroxide solution with a mass fraction of 8%-30%, and the specific mass fraction can be 8%, 10%, 15%, 20%, 25%, 30%, etc.

[0078] In some embodiments, after the secondary low-acid leaching reaction is completed, a second solid-liquid separation is performed to obtain a secondary low-acid leaching liquid and a secondary low-acid leaching residue, and the secondary low-acid leaching liquid is returned to the primary low-acid leaching stage and mixed with the pre-treated powder to make a pulp to recover the manganese element.

[0079] S4. Primary low-acid leaching solution treatment

[0080] The primary low-acid leaching solution obtained by the first solid-liquid separation is sequentially subjected to copper removal, ferrous iron removal and ferric aluminum removal to obtain an impurity-removed leaching solution, which can be directly used to prepare a positive electrode material precursor.

[0081] In some embodiments, the process of copper removal includes: mixing a low-acid leachate with nickel-iron elemental substance or nickel-iron powder for 1h-2h, then adding sulfuric acid to adjust the pH value to 0.5-1.0, stabilizing the pH value for 1h-4h under stirring, and then standing for 2h-4h to age the fine sponge copper to obtain a copper removal liquid. Nickel-iron elemental substance is a material obtained after a magnetic separation, and nickel-iron powder can be commercially available NPI powder. Compared with the traditional leachate iron powder copper removal, the embodiment of the present invention uses nickel-iron powder copper removal, which provides a new source of nickel source while realizing the copper removal function, and also reduces the introduction of system impurity iron, which greatly reduces the later impurity removal and solid waste iron and aluminum slag processing costs.

[0082] It should be noted that the effect of removing copper with nickel-iron powder is similar to that of removing copper with iron powder, but some incompletely reacted nickel-iron powder will remain in the generated sponge copper, resulting in unqualified sponge copper. The nickel-iron elemental powder used in the embodiment of the present invention is mainly derived from the high-matte nickel powder after a magnetic separation. After adding a certain amount of nickel-iron powder to remove copper, acid is continuously added to lower the pH value to consume the small amount of residual nickel-iron powder, which not only improves the utilization rate of the high-matte nickel raw material, but also saves iron powder auxiliary materials and ensures the quality of the sponge copper.

[0083] Specifically, the mixing reaction time of the primary low-acid leaching solution and nickel-iron element or nickel-iron powder can be 1.0h, 1.5h, 2.0h, etc.; thereafter, sulfuric acid is added to adjust the pH value to 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc.; the stabilization time can be 1h, 2h, 3h, 4h, etc.; and the standing time can be 2h, 3h, 4h, 5h, etc. without stirring.

[0084] In some embodiments, by regulating the amount of nickel iron or nickel iron powder added, the molar ratio of the total amount of nickel iron added to the copper ions in the primary low-acid leaching solution is 1: (0.5-1.5), such as 1: 0.5, 1: 0.8, 1: 1.0, 1: 1.2, 1: 1.5, etc. The total amount of nickel iron is controlled within the above range to more fully replace copper and improve the impurity removal effect.

[0085] Furthermore, the particle size of the nickel-iron powder is 60 mesh to 200 mesh, and the commercially available nickel-iron powder (NPI) can be crushed before being used for copper removal.

[0086] In some embodiments, the liquid after copper removal is mixed with hydrogen peroxide solution to remove ferrous iron, and the temperature is raised to 80°C-95°C and the pH value is adjusted to 3.8-4.5 to deeply remove iron and aluminum. Then, the calcium, magnesium, zinc and copper are removed by extraction. The impurities in the leachate are further removed by optimizing the impurity removal process to improve the purity of the product and avoid the influence of impurity elements. Specifically, the amount of hydrogen peroxide solution added can be calculated according to the content of ferrous iron in the leachate; the reaction temperature for controlling the deep removal of iron and aluminum can be 80°C, 85°C, 90°C, 95°C, etc., and the specific control of the reaction pH value can be 3.8, 4.0, 4.2, 4.5, etc., and the pH value can be adjusted by adding sodium carbonate solution.

[0087] In some embodiments, the process of removing ferrous iron includes: heating the liquid after the copper removal to 80°C-95°C, adding crude nickel hydroxide to adjust the pH value to 2.0-3.0, and adding a hydrogen peroxide solution with a mass fraction of 8%-30% to remove the remaining ferrous ions. Using crude nickel hydroxide (MHP) to adjust the pH value has the following three effects: using ferrous iron to react with the high-valent manganese slag in MHP that is difficult to leach, it not only cleverly oxidizes ferrous iron, but also improves the leaching effect of MHP; it can also consume the residual acid of the copper removal; it can also save soda ash (ie, sodium carbonate). The amount of hydrogen peroxide solution added is calculated according to the ferrous content in the liquid after the copper removal and the amount of nickel hydroxide to achieve the purpose of fully removing ferrous iron.

[0088] In summary, compared with traditional leaching raw materials, the embodiments of the present invention provide a broad supply source of nickel mainly using high-matte nickel, supplemented by crude nickel hydroxide (MHP) or cobalt hydroxide, and nickel iron powder (NPI), thereby avoiding over-reliance on the same supply source. A variety of combinations can better reduce the risk and cost of purchasing raw materials.

[0089] The embodiment of the present invention also provides a method for preparing a positive electrode material precursor, including using the leachate obtained by the leaching method provided by the embodiment of the present invention as a raw material, and adopting a coprecipitation method to prepare the positive electrode material precursor. Since the preparation cost of the leachate is low, it is beneficial to reduce the preparation cost of the positive electrode material precursor; the leachate provided by the embodiment of the present invention has a low impurity content, which can improve the purity of the precursor product and is beneficial to improving the electrochemical performance of the positive electrode material.

[0090] Specifically, the qualified wet process liquid obtained by the method of the present invention is added with a cobalt source and a manganese source, and the ratio is adjusted to synthesize a ternary precursor (nickel cobalt manganese hydroxide) through a hydrothermal synthesis method, thereby providing a new source of raw materials for a high-nickel ternary precursor.

[0091] In the actual operation process, metal salts can be added to the leaching solution according to the chemical formula of the target precursor, the proportions of elements such as nickel, cobalt and manganese can be adjusted, and complexing agents and precipitants can be added during the co-precipitation reaction to promote the co-precipitation reaction and obtain a precursor product with uniform particle size.

[0092] The embodiment of the present invention further provides a positive electrode material precursor, which is prepared by the above preparation method and has the advantages of low preparation cost and high product purity.

[0093] The embodiment of the present invention further provides a positive electrode material, which is prepared by the positive electrode material precursor provided by the embodiment of the present invention, and also has the advantages of low preparation cost and high product purity.

[0094] An embodiment of the present invention also provides a positive electrode plate, including the above-mentioned positive electrode material, and may also include a positive electrode current collector, a positive electrode active coating is formed on at least one surface of the positive electrode current collector, and the positive electrode material provided by the embodiment of the present invention exists in the positive electrode active coating as a positive electrode active material.

[0095] An embodiment of the present invention provides a secondary battery, including the above-mentioned positive electrode plate, and may also include a negative electrode plate, an electrolyte, a separator, etc. to form a complete battery structure with good cycle performance.

[0096] In other embodiments, the battery may not be in the form of a secondary battery, but may be in the form of a battery module, a battery pack, etc.

[0097] The embodiment of the present invention provides a device, including the above-mentioned secondary battery, battery module or battery pack, which can be used as a power source of the device or as an energy storage unit of the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0098] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0099] Example 1

[0100] This embodiment provides a method for leaching high-grade nickel matte, comprising the following specific steps:

[0101] (1) The composition of the provided nickel matte is as follows, in terms of mass fraction: nickel content is 47.92%, Co content is 1.19%, Mn content is 0.0187%, Cu content is 13.81%, Ca content is 0.6054%, and Fe content is 9%. The nickel matte is first coarsely crushed, and then crushed into a 100-400 mesh powder material by a conical ball mill. After the first magnetic separation, nickel-iron powder and the treated nickel matte powder are obtained.

[0102] (2) The high-nickel matte powder obtained after the first magnetic separation treatment is mixed with potassium permanganate at a ratio of 1:2, and a calcium carbonate buffer is added at a total weight of 3% (i.e., the mass ratio of the calcium carbonate buffer to the total amount of high-nickel matte powder and potassium permanganate is 3:100). The mixture is quantitatively configured in an alumina trough crucible, and a self-heating reaction is ignited in an air atmosphere (the ignition temperature is about 150°C). The reaction process continues until the potassium permanganate or high-nickel matte material is burned out, and the powder after the reaction is subjected to secondary magnetic separation to remove iron through a magnetic separation device.

[0103] (3) The material after secondary magnetic separation and iron removal (i.e., pre-treated powder) is subjected to a low-acid leaching, and the specific steps are as follows: the pre-treated powder is placed in a crucible, and tap water is sprayed at a solid-liquid mass ratio of 1:3. The slurry is introduced into the corresponding reaction tank, and tap water is added to the reaction tank as bottom water. The reaction container is a normal pressure steel-lined acid-resistant brick reaction tank. Concentrated sulfuric acid with a mass fraction of 98% is slowly added, and the mass ratio of the pre-treated powder to concentrated sulfuric acid is 1:1.2. The pH is adjusted to 0.5-1.0. After stabilization for 1 hour, crude nickel hydroxide (MHP, purchased from GEM) is added to adjust the pH value to 2.0-2.5. The reaction is carried out for 2 hours. The reaction temperature of the entire leaching process is 70°C. The nickel, cobalt and manganese in the leachate and the leaching residue are detected to obtain a qualified low-acid leaching slurry.

[0104] (4) The qualified low-acid leaching slurry after the reaction in step (3) is adjusted to a temperature of 85° C. and filtered through a membrane filter press to separate the low-acid leaching residue and the low-acid leaching liquid.

[0105] The low-acid leaching residue is mixed with concentrated sulfuric acid with a mass fraction of 98%, and the pH value is adjusted to 0.5-1.0. After adjusting the temperature to 60°C, it is mixed with a hydrogen peroxide solution with a mass fraction of 20% for reaction. After the pH value increases, concentrated sulfuric acid is added again for adjustment. Sulfuric acid and a reducing agent are repeatedly added to make the pH value 0.5-1.0, and secondary low-acid leaching is performed; after the secondary low-acid leaching reaction is completed, it is filtered to obtain a secondary low-acid leaching liquid and secondary low-acid leaching residue; the secondary low-acid leaching liquid is returned to the primary low-acid leaching stage and mixed with the pre-treated powder to prepare pulp.

[0106] After the chemical impurity removal process, the primary low-acid leaching solution is slowly supplemented with nickel-iron powder with a particle size of 100-150 meshes in a ratio of 1:1 to remove copper (the molar ratio of the total amount of nickel-iron to the copper content in the primary low-acid leaching solution is 1:1), react for 2 hours, add sulfuric acid to adjust the pH value to 0.5-1.0, stabilize under stirring conditions for 2 hours, and then stand for 4 hours before being transferred to an aging storage tank to enter the next process.

[0107] (5) The copper-free solution obtained in step (4) is heated to 90°C, and MHP (crude nickel hydroxide, purchased from GEM) is added to adjust the pH to 2.0-2.5. After stabilization for 2 hours, 8% by mass of hydrogen peroxide is added to oxidize ferrous iron according to the residual ferrous iron content, and the temperature is controlled at 80°C to 95°C. Soda ash solution is added to adjust the pH to 3.8 to 4.2 to remove iron and aluminum. After stabilization for 1 hour, after solid-liquid separation, the obtained wet process liquid is further subjected to extraction to remove calcium, magnesium, zinc and copper to obtain a qualified wet process liquid. The specific operation steps of extracting calcium, magnesium, zinc and copper are as follows (the same below): the wet process liquid is subjected to P204 extraction to remove calcium, zinc and copper to obtain a manganese sulfate solution (obtained by organic phase reverse extraction), the first stage raffinate is subjected to P507 extraction to separate cobalt to obtain a cobalt sulfate solution, the second stage raffinate is subjected to C272 to separate magnesium, and the third stage raffinate is subjected to P507 to separate nickel to obtain a nickel sulfate solution, and the three are mixed to obtain the required nickel, cobalt and manganese sulfate solution.

[0108] (6) Add 10% ammonia solution, 30% sodium hydroxide solution and water into the reactor as the bottom liquid, and control the ammonia concentration of the bottom liquid to be 10% and the pH value to be 8. Add nickel sulfate, cobalt sulfate and manganese sulfate to the obtained qualified wet process liquid in a molar ratio of 8:1:1 to prepare a nickel-cobalt-manganese mixed solution with a total concentration of 100 g / L, add the nickel-cobalt-manganese mixed solution, ammonia solution and sodium hydroxide solution into the reactor respectively, and introduce nitrogen as a protective gas. Adjust the pH in the reactor to 10, the ammonia concentration to 10%, the temperature to 50°C-60°C, the stirring speed to 150 r / min, and conduct a nucleation reaction in the reactor (control the residence time by the nucleus generator so that the reaction only generates nuclei without growth) to obtain a slurry. A program for configuring the kettle to overflow in series is designed, and the prepared slurry overflows into the growth kettle, so that the nuclei of the ternary precursor can grow without generating new nuclei; the slurry of the growth kettle overflows into the synthesis kettle (the reactor used in the synthesis process), and after precipitation, washing, separation and drying, 8 series ternary precursors are obtained.

[0109] Example 2

[0110] This embodiment provides a method for leaching high-grade nickel matte, comprising the following specific steps:

[0111] (1) The composition of the provided nickel matte is as follows, in terms of mass fraction: nickel content is 47.92%, Co content is 1.19%, Mn content is 0.0187%, Cu content is 13.81%, Ca content is 0.6054%, and Fe content is 9%. The nickel matte is first coarsely crushed and then crushed into a powder material of 100 to 400 meshes by a conical ball mill.

[0112] (2) The ground nickel matte powder is mixed with potassium permanganate in a ratio of 1:2, and the mixture is quantitatively configured in an alumina trough crucible. The mixture is ignited in an air atmosphere to cause a self-heating reaction (ignition temperature is about 150°C). The reaction process continues until the potassium permanganate or nickel matte material is burned out.

[0113] (3) subjecting the material obtained in step (2) to a low-acid leaching, specifically comprising the following steps: according to the amount of material configured in the crucible, spraying tap water at a solid-liquid mass ratio of 1:3, introducing the slurry into a corresponding reaction tank, adding tap water as bottom water to the reaction tank, the reaction vessel being a normal pressure steel-lined acid-resistant brick reaction tank, slowly adding 98% concentrated sulfuric acid by mass, the mass ratio of the pretreatment powder to the concentrated sulfuric acid being 1:1.2, adjusting the pH to 0.5-1.0, stabilizing for 1 hour, then adding cobalt hydroxide to adjust the pH to 2.0-2.5, reacting for 2 hours, the reaction temperature of the entire leaching process being 70°C, detecting nickel, cobalt and manganese in the leachate and the leaching residue, and obtaining a qualified low-acid leaching slurry;

[0114] (4) The qualified low-acid leaching slurry after the reaction in step (3) is adjusted to a temperature of 85° C. and filtered through a membrane filter press to separate the low-acid leaching residue and the low-acid leaching liquid.

[0115] The low-acid leaching residue is subjected to a secondary low-acid leaching process: the low-acid leaching residue is mixed with concentrated sulfuric acid with a mass fraction of 98%, the pH value is adjusted to 0.5-1.0, the temperature is adjusted to 60°C, and then mixed with a hydrogen peroxide solution with a mass fraction of 20% for reaction, and after the pH value increases, concentrated sulfuric acid is added to adjust it, and sulfuric acid and a reducing agent are repeatedly added to make the pH value 0.5-1.0, and secondary low-acid leaching is performed; after the secondary low-acid leaching reaction is completed, it is filtered to obtain a secondary low-acid leaching liquid and secondary low-acid leaching residue; the secondary low-acid leaching liquid is returned to the primary low-acid leaching stage and mixed with the pre-treated powder to make pulp;

[0116] After the chemical impurity removal process, the primary low-acid leaching solution is slowly supplemented with nickel-iron powder with a particle size of 100-150 meshes in a ratio of 1:1 to remove copper (the molar ratio of the total amount of nickel-iron to the copper content in the primary low-acid leaching solution is 1:1), react for 2 hours, add sulfuric acid to adjust the pH value to 0.5-1.0, stabilize under stirring conditions for 2 hours, and then stand for 4 hours before being transferred to an aging storage tank to enter the next process.

[0117] (5) The copper-free solution obtained in step (4) is heated to 90°C, and MHP (crude nickel hydroxide, purchased from GEM) is added to adjust the pH to 2.0-2.5. After stabilization for 2 hours, 8% by mass of hydrogen peroxide is added to oxidize the ferrous iron according to the residual ferrous iron content, and the temperature is controlled at 80°C to 95°C. Soda ash solution is added to adjust the pH to 3.8 to 4.2 to remove iron and aluminum. After stabilization for 1 hour, after solid-liquid separation, the obtained wet process liquid is further subjected to extraction to remove calcium, magnesium, zinc and copper to obtain a qualified wet process liquid. The specific operation steps of extracting calcium, magnesium, zinc and copper are as follows (the same below): the wet process liquid is subjected to P204 extraction to remove calcium, zinc and copper to obtain a manganese sulfate solution (obtained by organic phase reverse extraction), the first stage raffinate is subjected to P507 extraction to separate cobalt to obtain a cobalt sulfate solution, the second stage raffinate is subjected to C272 to separate magnesium, and the third stage raffinate is subjected to P507 to separate nickel to obtain a nickel sulfate solution, and the three are mixed to obtain the required nickel cobalt manganese sulfate solution.

[0118] (6) The specific steps are the same as those in Example 1.

[0119] Example 3

[0120] The only difference from Example 2 is that in step (4), the nickel-iron powder is replaced by iron powder, and the molar ratio of iron to copper is controlled to be 1:1.

[0121] Example 4

[0122] The only difference from Example 1 is that the pre-treated material is not subjected to magnetic separation for iron removal (ie, no primary magnetic separation and secondary magnetic separation are performed).

[0123] Example 5

[0124] The only difference from Example 1 is that iron powder is used in the first copper removal process.

[0125] Comparative Example 1

[0126] The only difference from Example 1 is that no oxidant is added in the pretreatment step, calcination is carried out at 1000° C. in an oxygen atmosphere for 4 hours, and then low-acid leaching is carried out.

[0127] Comparative Example 2

[0128] The only difference from Example 1 is that the high-grade nickel matte is not subjected to a pretreatment process (i.e., steps (1) and (2) are not performed) and is directly leached with low acid.

[0129] Comparative Example 3

[0130] This comparative example provides a traditional high-grade nickel matte leaching process, and the specific steps are as follows:

[0131] (1) The composition of the provided high-grade nickel matte is as follows: nickel content is 47.92%, Co content is 1.19%, Mn content is 0.0187%, Cu content is 13.81%, Ca content is 0.6054%, and Fe content is 9%. The high-grade nickel matte is first coarsely crushed, and then crushed into a 60-mesh to 200-mesh powder material by a conical ball mill, and mixed according to the mass ratio of high-grade nickel matte powder to lithium manganate electrode powder = 1:1, and then roasted in a rotary kiln, the roasting temperature is set at 200°C, and the firing time is 60 minutes. After the first roasting, the material is roasted in the second stage, and the roasting temperature is set at 400°C. When the roasting reaches 90 minutes in the middle, water is sprayed once, and the water amount is controlled to be 5% of the total weight of the material. The firing time is 180 minutes, and the protective atmosphere is air. After cooling, the high-grade nickel matte pre-treatment powder is obtained.

[0132] (2) The pre-treated high-grade nickel matte powder is mixed with positive electrode material powder in a mass ratio of 1:2, concentrated water is added as base water, and slurry is prepared at a solid-liquid ratio of 1:3 (other ratios are also acceptable, but the leaching rate is slightly different). The reaction vessel is a normal pressure steel-lined acid-resistant brick reaction tank. Sulfuric acid is added repeatedly to adjust the pH to 0.5-1.0, and unqualified ternary precursors are added to adjust the pH to 2.0 to 2.5. 50 kg of filter aid is added, and the temperature is raised to 80°C to obtain a low-acid leaching slurry.

[0133] (3) The reaction solution was filtered through a membrane filter press with a filtration efficiency of 20 m 3 / h, separate low-acid leaching residue and low-acid leaching liquid, the low-acid leaching residue is subjected to the atmospheric pressure high-acid leaching process, the high-acid leaching liquid returns to the atmospheric pressure low-acid leaching step and is mixed with the pre-treated powder to make pulp, the low-acid leaching liquid is subjected to a chemical impurity removal process, iron powder is added to remove copper once, 8% hydrogen peroxide is used to oxidize ferrous iron, the temperature is controlled at 80°C to 95°C, unqualified precursors are added to adjust the pH to 3.0 to 3.5, and then soda ash solution is added to adjust the pH to 3.8 to 4.2 to remove iron and aluminum. After solid-liquid separation, the obtained wet process liquid is further extracted to remove calcium, magnesium and zinc, and the raffinate is used to remove lithium to obtain a qualified wet process liquid.

[0134] (4) 1 / 3 of sodium borohydride with a mass concentration of 0.5wt%, 1 / 3 of ammonia water with a mass concentration of 6wt%, water and sodium hydroxide are mixed and added to a reactor as a base liquid, cobalt sulfate and manganese sulfate are added to the obtained qualified wet process liquid to prepare a nickel-cobalt-manganese mixed solution with a nickel-cobalt-manganese molar ratio of 6:2:2 and a total nickel-cobalt-manganese concentration of 100g / L, and then the mixed solution is mixed with the remaining ammonia water and sodium borohydride and added to the reactor, and nitrogen is introduced as a protective gas.

[0135] (5) The pH in the reactor is adjusted to 10.1, the temperature to 50°C-60°C, and the stirring speed to 250 r / min. A nucleation reaction is carried out in the reactor (the residence time is controlled by a nucleus generator so that only nuclei are generated without growth) to obtain a slurry. A program for configuring the reactor to overflow in series is designed to allow the obtained slurry to overflow into the growth reactor, so that the nuclei of the ternary precursor can grow without generating new nuclei. The slurry in the growth reactor is overflowed into the synthesis reactor (the reactor used in the synthesis process), and after precipitation, washing, separation and drying, a 6-series ternary precursor is obtained.

[0136] Test Example 1

[0137] The leaching effects of the above embodiments and comparative example leaching methods were tested, and the results are shown in Table 1.

[0138] Test method:

[0139] (1) Low acid leaching nickel leaching rate: atomic absorption spectrometry;

[0140] (2) Copper removal effect: atomic absorption spectroscopy.

[0141] Table 1 Leaching effect of the leaching method of the embodiment and the comparative example

[0142] Low acid leaching nickel leaching rate Low acid reaction time (h) Copper removal effect Copper removal reaction time (h) Example 1 95.4% 3 97.4% 2 Example 2 95.1% 3 95.8% 2 Example 3 94.5% 3 94.9% 2 Example 4 95.2% 3 97.2% 2 Example 5 95.3% 3 96.5% 2 Comparative Example 1 72.5% 12 95.7% 2 Comparative Example 2 30.2% 12 96.1% 2 Comparative Example 3 75.5% 8 95.2% 2

[0143] It can be seen that the leaching rate of the leaching method provided by the embodiment of the present invention is very high, the low-acid leaching time is short, and the copper removal effect is also ideal.

[0144] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for leaching high-grade nickel matte, characterized in that: include: Raw material pretreatment: Mix high nickel matte with oxidant for autothermal reaction; Primary low-acid leaching: The powder obtained by the pretreatment of the raw material is subjected to a primary low-acid leaching under non-pressurized conditions, and the pH value of the leaching is controlled to be 0.5-1.

0.

2. The leaching method according to claim 1, characterized in that The raw material pretreatment process includes: subjecting high-grade nickel matte to a magnetic separation to obtain nickel iron and high-grade nickel matte powder; mixing the high-grade nickel matte powder with an oxidant and a buffer for autothermal reaction to obtain a pretreatment intermediate powder; subjecting the pretreatment intermediate powder to a secondary magnetic separation to obtain a pretreatment powder; During the raw material pretreatment process, at least one of features A1 to A7 is satisfied: Feature A1: Firstly, the high nickel matte is crushed to a particle size of 100-400 mesh, and then the magnetic separation is performed; Feature A2: The oxidant is selected from at least one of potassium permanganate and sodium permanganate; Feature A3: The mass ratio of the high nickel matte powder to the oxidant is 1:(1-3); Feature A4: The buffer is selected from at least one of calcium carbonate and calcium hydroxide; Feature A5: The mass ratio of the buffer to the total amount of the high nickel matte powder and the oxidant is (1-10): 100; Feature A6: The reaction time of the autothermal reaction is 50min-120min; Feature A7: The autothermal reaction is carried out under an air atmosphere.

3. The leaching method according to claim 2, characterized in that The process of the primary low-acid leaching comprises: leaching the pre-treated powder in a sulfuric acid solution; After 1h-2h of reaction, the first solid-liquid separation is performed; Or, after reacting for 1h-2h, add pre-treated powder to adjust the pH value to 2.0-2.5, react for 2h-3h, and then perform the first solid-liquid separation; Alternatively, after reacting for 0.5 h to 2.0 h, crude nickel hydroxide or crude cobalt hydroxide is added to adjust the pH value to 2.0 to 2.5, reacting for 2 h to 3 h, and then performing the first solid-liquid separation.

4. The leaching method according to claim 3, characterized in that The pre-treated powder is mixed with water and concentrated sulfuric acid, and the obtained slurry is reacted at a pH value of 0.5-1.0; During the one low-acid leaching process, at least one of the characteristics B1 to B5 is met: Feature B1: The mass ratio of the pre-treated powder to water is 1:(1-4); Feature B2: The mass ratio of the pre-treated powder to the concentrated sulfuric acid is 1:(1.0-1.5), and the mass fraction of the concentrated sulfuric acid is greater than or equal to 98%; Feature B3: The reaction temperature of the primary low-acid leaching is 50°C-90°C; Feature B4: Before the first solid-liquid separation, the temperature of the material after the reaction is adjusted to 80°C-90°C; Feature B5: The first solid-liquid separation is carried out in a membrane filter press.

5. The leaching method according to claim 3, characterized in that: Also includes: The low-acid leaching residue obtained by the first solid-liquid separation is mixed with sulfuric acid to adjust the pH value to 0.5-1.0, the temperature is adjusted to 50° C.-70° C., and then mixed with a reducing agent for reaction, sulfuric acid and the reducing agent are repeatedly added to adjust the pH value to 0.5-1.0, and a secondary low-acid leaching is performed; Preferably, after the secondary low-acid leaching reaction is completed, a second solid-liquid separation is performed to obtain a secondary low-acid leaching liquid and a secondary low-acid leaching residue; the secondary low-acid leaching liquid is returned to the primary low-acid leaching stage and mixed with the pre-treated powder to prepare a slurry; Preferably, the reducing agent is a hydrogen peroxide solution with a mass fraction of 8%-30%.

6. The leaching method according to claim 3, characterized in that: The primary low-acid leaching solution obtained by the first solid-liquid separation is subjected to sequential removal of copper, ferrous iron and iron-aluminum to obtain a decontaminated leaching solution; Preferably, the copper removal process comprises: mixing the primary low-acid leaching solution with the nickel-iron element or nickel-iron powder for reaction for 1h-2h, then adding sulfuric acid to adjust the pH value to 0.5-1.0, and standing for 2h-4h to obtain a primary copper removal solution; More preferably, the pH is stabilized for 1 h to 4 h under stirring before standing for 2 h to 4 h; More preferably, by regulating the amount of the nickel-iron element or the nickel-iron powder added, the molar ratio of the total amount of nickel-iron added to the copper ions in the primary low-acid leaching solution is 1:(0.5-1.5); More preferably, the particle size of the nickel-iron powder is 60 mesh-200 mesh.

7. The leaching method according to claim 6, characterized in that The copper removal solution is mixed with hydrogen peroxide solution to remove ferrous iron, the temperature is raised to 80° C.-95° C., the pH value is adjusted to 3.8-4.5 to deeply remove iron and aluminum, and then the calcium, magnesium, zinc and copper are removed by extraction; Preferably, the process of removing ferrous iron comprises: heating the solution after the copper removal to 80°C-95°C, adding crude nickel hydroxide to adjust the pH value to 2.0-3.0, and adding a hydrogen peroxide solution with a mass fraction of 8%-30% to remove the remaining ferrous iron ions; Preferably, the pH value is adjusted to 3.8-4.5 by adding sodium carbonate solution.

8. A method for preparing a positive electrode material precursor, characterized in that: The method comprises using the leachate obtained by the leaching method according to any one of claims 1 to 7 as a raw material and adopting a co-precipitation method to prepare the positive electrode material precursor; Preferably, metal salt is added to the leaching solution, and a complexing agent and a precipitant are added during the coprecipitation reaction.

9. A cathode material precursor, characterized in that: It is prepared by the preparation method described in claim 8.

10. A positive electrode material, characterized in that: It is prepared by the positive electrode material precursor described in claim 9.

Citation Information

Patent Citations

  • Method for leaching copper and nickel in leaching slag of matte / ice nickel with assistance of microwave

    CN103725889A

  • process for the recovery of the metallic constituents of a material such as an ore

    FR1258467A